ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MAHASISWA DALAM MEMILIH PROGRAM STUDI PADA JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI BANJARMASIN - Muhammad Teguh Nuryadin; Marijati Sangen; Siti Aliyati Albushairi (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
This study aims to identify and analyze factors affecting the decisions of the students in selecting courses (Y) with a focus on Brand Equity factor (X1) consist ing of Brand Awareness, Brand Loyalty, Perceive Quality, Brand Association and Factors of Reference Group (X2 ) which are Normative and Informational. Then, they are analyzed using factor analysis resulting in the formation of new factors at the Department of Business Administration, State Polytechnic Banjarmasin. This research method used explanatory research by distributing questionnaires to the samples of respondents, students of the Department of Business Administration. The department consists of three study programs: Business Administration, Informative Management and Banking. The number of samples were 100 people (purposive sampling). Then the data were analyzed using factor analysis which resulted in the formation of new factors that indicated factors of brand loyalty (X1), Normative and Informational reference groups (X2), brand awareness (X3), Brand Asosiation (X4), the influence of external environment (X5), quality of human resources (X6), and atmosphere and learning facility factors (X7), and then the analysis was followed by multiple linear regression analysis to determine the effects simultaneously and partially of the newfactors to the decisions in choosing a study program at the Department of Business Admninistration, State Polytechnic Banjarmasin. The results showed that factors of of brand loyalty (X1), normative and informational reference groups (X2), brand awareness (X3), brand association (X4), the influence of external environment (X5), quality of human resources (X6), and atmosphere and learning facility factors (X7) simultaneously gave significant effects on the decisions in choosing study programs in Business Administration Department, State Polytechnic Banjarmasin. Partially, brand loyalty (X1), normative and informational reference groups (X2), brand awareness (X3), the influence of external environment (X5) significantly influence the decisions in choosing study programs (Y). and brand asosiation (X4), quality of human resources (X6) and atmosphere and learning facility factors (X7) partially did not affect the decisions in selecting a study program (Y).